2012
DOI: 10.7740/kjcs.2012.57.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Isoflavone Contents During Maturation under Different Planting Dates in Black Soybean

Abstract: This study was carried out to investigate the influence of different planting time on the synthesis of isoflavone in black soybean, Three varieties used in this experiment were lpumgeomjeongkong, Cheongjakong and Heugcheongkong which had different ecotypes, repectively. Seeds were sown at different time, May 15th, May 30th and June 15th with planting density of 60x15cm. In order to analyze the content of isoflavone, we collected sample every 5 days from 30 days after flowering to harvest and analyzed them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…These results suggest that diverse interactions of individual soybean cultivars with the ecological environment during the ripening period based on the planting time might influence the synthesis and accumulation of isoflavone. Yi and Yoon (2012) found that the variations in the time and speed of isoflavone accumulation were different based on the soybean cultivars or planting time when monitored until maturation after flowering of black soybean cultivars.…”
Section: Variation In Isoflavone Content Of Soybean Cultivar Groups Amentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that diverse interactions of individual soybean cultivars with the ecological environment during the ripening period based on the planting time might influence the synthesis and accumulation of isoflavone. Yi and Yoon (2012) found that the variations in the time and speed of isoflavone accumulation were different based on the soybean cultivars or planting time when monitored until maturation after flowering of black soybean cultivars.…”
Section: Variation In Isoflavone Content Of Soybean Cultivar Groups Amentioning
confidence: 99%
“…The same cultivar can have different isoflavone contents, which is influenced by environmental factors. In particular, different levels of isoflavone content have been reported based on the cultivation environments such as planting time and fertilization level, different weather conditions, and the altitude of the cultivation area (Hasanah et al 2015;Lee et al 2003;Yi and Yoon 2012;Yun et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…작물 의 재배환경에 대한 연구로는 재배환경에 따른 보리의 β -glucan 함량에 관한 연구 에서 β-glucan 함량은 재배지역에 따라 큰 차이가 없는 것으로 보고하였으 며, 쌀의 이화학적 특성에 관한 연구 (Kim & Lim, 1987)에 서 품종별 아밀로그램 특성이 차이가 있는 것으로 보고하였 다. 또한 검정콩에 함유된 안토시아닌의 함량을 재배지역 (Yi et al, 1997) 및 고도 (Shin et al, 2009) (Dewanto et al, 2002). 각 추출물 50 μL 에 2% Na2CO3 용액 1 mL를 가한 후 3분간 방치하여 50% (Fig.…”
unclassified